2005
DOI: 10.1242/jcs.01667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of trichoplein, a novel keratin filament-binding protein

Abstract: Keratins 8 and 18 (K8/18) are major components of the intermediate filaments (IFs) of simple epithelia. We report here the identification of a novel protein termed trichoplein. This protein shows a low degree of sequence similarity to trichohyalin, plectin and myosin heavy chain, and is a K8/18-binding protein. Among interactions between trichoplein and various IF proteins that we tested using two-hybrid methods, trichoplein interacted significantly with K16 and K18, and to some extent with K5, K6a, K8 and K14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 46 publications
5
81
0
Order By: Relevance
“…1B,C). These staining patterns confirm the previous observation that trichoplein localizes to keratin IFs and desmosomes in the epithelia (Nishizawa et al, 2005).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1B,C). These staining patterns confirm the previous observation that trichoplein localizes to keratin IFs and desmosomes in the epithelia (Nishizawa et al, 2005).…”
Section: Resultssupporting
confidence: 91%
“…Nishizawa and colleagues (Nishizawa et al, 2005) previously reported that trichoplein keratin filament-binding protein (trichoplein or TCHP) serves as a keratin IF scaffold protein.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to plectin and H3 histones, trichoplein and Albatross were also identified as CK8/18-binding proteins (32,33). Trichoplein shows a low degree of sequence similarity to trichohyalin, plectin, and myosin heavy chain, and colocalizes with CK8/18 filaments in HeLa cells (32).…”
Section: Interactions With Related Proteinsmentioning
confidence: 99%
“…Trichoplein shows a low degree of sequence similarity to trichohyalin, plectin, and myosin heavy chain, and colocalizes with CK8/18 filaments in HeLa cells (32). Trichoplein may be involved in the organization of the apical network of keratin filaments and desmosomes in simple epithelial cells (32). Albatross (also known as Fas-binding factor-1) also has a trichohyalin and plectin homology (TPHD) domain, which binds to CK18 directly in a yeast two-hybrid system.…”
Section: Interactions With Related Proteinsmentioning
confidence: 99%
“…healing, and overall tissue integrity (McLean et al, 1996;Boudreau and Bissell, 1998;Gallicano, 2001;Gallicano et al, 2001;Leung et al, 2002;Grossmann et al, 2004;Setzer et al, 2004;Weber et al, 2004;Nishizawa et al, 2005). One of the oldest known, and yet still growing, family of cytoskeletal crosslinking proteins is the plakin family (Leung et al, 2002).…”
Section: Fig 1 Kaz Colocalizes To the Spindle Apparatusmentioning
confidence: 99%